Islamic Economics in Indonesia: Exploring the Philosophical Contributions of Imam Al-Ghazali and Imam Al-Mawardi - Nur Arbaien, Muhamad Fasya; Dafi, Imam Ahmad; Ramlan Sandiyana, Dede San San; Latifa, Mutia; Nurkaromah, Silvia Ripa (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2024)
The method used in this article is a comparative method with a qualitative approach. The data sources used in this study are secondary data. The data analysis technique employed is content analysis, done by in-depth discussion of the written information. The results of this research show that the thoughts of Imam Al-Ghazali and Imam Al-Mawardi in Islamic economics have similarities and differences. Al-Ghazali's view on social welfare and state regulation of the market aligns with the Indonesian government's efforts to achieve social justice. On the other hand, Al-Mawardi's thoughts on the state's role in meeting the correlated needs of citizens and the taxation system are relevant to Indonesia's efforts to improve the economic system.